Southeast Asian Ceramics Museum : (Bangkok University Press, 2009)
The Southeast Asian Ceramics Museum was established with the aim to be a learning center of ancient works of art for those who are interested in archeology, as well as to serve as a research center and a place for displaying highly valuable collections of cultural evidence.